2016
DOI: 10.2147/ijgm.s114577
|View full text |Cite
|
Sign up to set email alerts
|

Thicker carotid intima-media thickness and increased plasma VEGF levels suffered by post-acute thrombotic stroke patients

Abstract: Background and objectivesAtherosclerosis causes reduction of the oxygen supply to structures in the far arterial wall, provoking the release of factors that drive angiogenesis of vasa vasorum, including VEGF. Other studies have revealed the inflammatory response in atherosclerosis and the role of platelet factor 4 (PF4) as an anti-angiogenic chemokine through the inhibition of VEGF. This cross-sectional study aims at measuring the effect of atherosclerosis assessed through carotid intima-media thickness (CIMT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Stroke was the leading cause of death and the third most common cause of disability in China between 1990 and 2017 (1,2). The most common type of stroke is thrombotic stroke, and atherosclerosis is the most common cause (3). Thus, early detection and management of individuals at high risk is critical to prevent or delay otherwise inevitable end-events.…”
Section: Introductionmentioning
confidence: 99%
“…Stroke was the leading cause of death and the third most common cause of disability in China between 1990 and 2017 (1,2). The most common type of stroke is thrombotic stroke, and atherosclerosis is the most common cause (3). Thus, early detection and management of individuals at high risk is critical to prevent or delay otherwise inevitable end-events.…”
Section: Introductionmentioning
confidence: 99%
“…Another study [59] failed to confirm a change in plasma VEGF levels and anatomical location of the coronary artery, aortic root, coronary sinus, and femoral vein immediately after angioplasty in CAD cases. Similarly, in another study [60], there was no significant correlation between plasma VEGF levels and carotid intima-media thickness in post-acute thrombotic stroke cases 90 days after stroke onset. The authors concluded that plasma VEGF cannot specifically assess vascular status because it can be induced by ischemic conditions in tissues throughout the body.…”
Section: Discussionmentioning
confidence: 78%
“…Increased VEGF values in atherothrombotic stroke patients were observed without a significant correlation with carotid IMT value in the post-acute phase [167].…”
Section: Pregnancy-associated Plasma Protein-a (Pappmentioning
confidence: 79%